PENINGKATAN PARTISIPASI AKTIF SISWA MELALUI PENERAPAN PENDEKATAN ILMU TEKNOLOGI MASYARAKAT (ITM) DALAM PEMBELAJARAN IPS DI SD KELAS TINGGI - Panni Resnawati (Universitas Negeri Medan, 2022)
Abstract:Analysis of Increasing Student Active Participation through the Application of the Science Technology Society (STS) Approach in Social Studies Learning in High School Elementary Schools. The purpose of the study was to analyze the application of the Science Technology Society (STS) approach to determine the increase in students active participation in social studies learning in high school elementary schools. The research subjects are high school elementary school students, the sample taken is grade 4. The research method used is descriptive analysis of the type of study literature where the data collection process comes from secondary data literature. This study uses content analysis techniques (content analysis). The results of the study illustrate that there is an increase in student active participation through the application of the Science Technology Society (STS) approach in social studies learning in high school elementary schools. The Science Technology Society (STS) approach requires students to construct, identify, design, create, and implement their knowledge into new knowledge, which can be obtained by students from active participation during the learning process. Abstrak:Analisis Peningkatan Partisipasi Aktif Siswa melalui Penerapan Pendekatan Ilmu Teknologi Masyarakat (ITM) dalam Pembelajaran IPS di SD Kelas Tinggi. Tujuan penelitian adalah menganalisis penerapan pendekatan Ilmu Teknologi Masyarakat untuk mengetahui peningkatan partisipasi aktif siswa dalam pembelajaran IPS di SD kelas tinggi. Subjek penelitian yaitu siswa Sekolah Dasar (SD) kelas tinggi, sample yang diambil adalah kelas 4. Metode penelitian yang digunakan adalah analisis deskriprif tipe study literature dimana proses pengambilan data berasal dari literatur data sekunder. Penelitian ini menggunakan teknik analisis isi (content analysis). Hasil penelitian memberikan gambaran bahwa adanya peningkatan partisipasi aktif siswa melalui penerapan pendekatan Ilmu Teknologi Masyarakat (ITM) dalam pembelajaran IPS di SD kelas tinggi. Pendekatan ITM tersebut menuntut siswa untuk mengkontruksi, mengidentifikasi, merancang, mencipta, dan mengimplementasikan pengetahuan yang dimiliki ke dalam pengetahuan baru, yang dapat diperoleh siswa dari partipasi akif selama proses pembelajaran berlangsung.